Bruton’s Tyrosine Kinase (BTK) Inhibitors and Autoimmune Diseases: Making Sense of BTK Inhibitor Specificity Profiles and Recent Clinical Trial Successes and Failures - Ringheim, Garth E.; Wampole, Matthew; Oberoi, Kinsi (Frontiers in Immunology, 2021)
Clinical development of BTK kinase inhibitors for treating autoimmune diseases has lagged those observed for their use in the treatment of cancer due in part from lack of selectivity and associated toxicity profiles of first generation drug candidates. Second generation BTK inhibitors have made great strides in limiting off-target activities for distantly related kinases, though variable success at limiting cross-reactivity within the more closely related TEC family of kinases. We investigated the BTK specificity and toxicity profiles, drug properties, disease associated signaling pathways, clinical indications, and trial successes and failures for the 13 BTK inhibitor drug candidates tested in phase 2 or higher clinical trials representing 9 autoimmune disease indications. We focused on rheumatoid arthritis (RA), multiple sclerosis (MS), and systemic lupus erythematosus (SLE) where the majority of BTK pre-clinical and clinical studies have been reported, with additional information for pemphigus vulgaris (PV), Sjogren’s disease (SJ), chronic spontaneous urticaria (CSU), graft versus host disease (GVHD), and asthma included where available. While improved BTK selectivity versus kinases outside the TEC family improved clinical toxicity profiles, less toxicity profile distinction was evident within the TEC family. Analysis of genetic associations of RA, MS, and SLE biomarkers with TEC family members revealed that BTK and TEC family members may not be drivers of disease. They are, however, mediators of signaling pathways within the pathophysiology for autoimmune diseases and furthermore BTK may be associated with B cell and myeloid differentiation as well as autoantibody driven diseases. Successes in the clinic for treating RA, MS, PV, ITP, and GVHD, but not for SLE and SJ support the concept that BTK is an essential and sufficient determinant for these autoimmune indications. Based on the data collected in this study, we propose that current compound characteristics of BTK inhibitor drug candidates for the treatment of autoimmune diseases have achieved the selectivity, safety, and coverage requirements necessary to achieve therapeutic benefit.